2017
DOI: 10.1088/1757-899x/223/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and mophology natural rubber blend with bentonit and carbon black

Abstract: Abstract. Purpose of this study was to determine the mechanical properties and morphology of composite natural rubber and natural bentonite with addition of Na-bentonite filler and carbon black to natural rubber. The method is carried material mixed with filler composition variations (0,10,20,30) phr using open mill for 6 min. Results of the open mill is vulcanized at a temperature of 170 o C. Further testing mechanical properties and morphology. Results showed that the addition of Na-bentonite filler and carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This restricts the mobility of chains hence causes lower percentage elongation values. 36,37 N339 nanofillers reinforced rubber composites show a maximum stretchability of about 460% due to good compatibility of polymeric chains of rubber and N339 nanofillers.
Figure 8.Variation in elongation of different rubber compounds containing carbon black nanofillers.
…”
Section: Resultsmentioning
confidence: 99%
“…This restricts the mobility of chains hence causes lower percentage elongation values. 36,37 N339 nanofillers reinforced rubber composites show a maximum stretchability of about 460% due to good compatibility of polymeric chains of rubber and N339 nanofillers.
Figure 8.Variation in elongation of different rubber compounds containing carbon black nanofillers.
…”
Section: Resultsmentioning
confidence: 99%
“…Bukit et al [8] found that the application of bentonite as nanofillers for high density polyethylene (HDPE) polymeric system could enhance the mechanical properties of the system with the best performance at 2-6 wt % of bentonite. Similarly, Ginting et al [9] discovered that the addition of Na-bentonite filler and carbon black could influence the rubber. Related to that, the utilization of bentonite to other polymeric systems needs to be conducted in order to develop the study about polymer nanocomposites.…”
mentioning
confidence: 94%
“…For example, combining bentonite/rice husk in the HDPE matrix can improve the mechanical properties of the composite [6]. In addition, combining bentonite with carbon black, which is used as a natural rubber filler, can affect tensile strength, elongation at break, modulus of elasticity, and composite hardness [7,8]. In addition, the addition of nano SiO 2 and bentonite was able to increase the compressive strength of the mortar [9].…”
Section: Introductionmentioning
confidence: 99%